Analysis of Digital Economy Determinants in Indonesia - Ahmad Albar Tanjung; Muliyani Muliyani; Nurhayati Nurhayati; Wulan Fitri Nasution; Mutiara Y. Br. Ginting (PT Mattawang Mediatama Solution, 2023)
The aims of this research is to determine the digital economy in Indonesia which consist of e-commerce, financial technology, and the number of internet users. This research was descriptive statistical method and using panel data regression model. The period of this research starts from 2020-2022 with cross-sectional data from 34 provinces in Indonesia. The data was collected from the Central Bureau of Statistics and East Ventures. The results of this study indicate that e-commerce has a positive and significant effect on the digital economy, financial technology has a positive and significant effect on the digital economy, the number of internet users has a positive and insignificant effect on the digital economy in Indonesia. This research provides a new insight of the role of e-commerce in economic growth and the importance of government policy and intervention in promoting local products on various e-commerce platforms. The low level of digital literacy in Indonesia required the role of academics and practitioners to participate in establish a smart technology society.